Micrometeorological modelling in urban areas - Martilli, Alberto; Santiago, Jose Luis; Martín, Fernando (Física de la Tierra, 2008)
Micrometeorological studies in urban zones are more complex than in rural zones. Inside urban canopy, 3-D flow structures are created by the urban geometry (streets with different configurations of buildings). In this paper, the application of microscale models (CFD models) to urban micrometeorology is studied and a CFD model is applied to an array of cubes representing a portion of a city. The model results are validated against wind tunnel measurements made with the same geometry and are analysed to understand the flow properties in this case. Strong horizontal inhomogeneities of the mean and turbulence variables are found inside the canyons showing that the representativeness of measurement in one point is limited spatially. In addition, the CFD results are spatially averaged over thin slices encompassing a cube-canyon unit in the central zone of the array showing the special importance of average properties as the dispersive stress inside the urban canopy created by the cubes.